A New Burial Find of a Polovtsian Stone Statue in the Stavropol Region (from the second half of thirteenth to fourteenth century) - Berezin Ya.B.; Narozhny E.I. (Золотоордынское обозрение)
Research objectives: To introduce a new discovery of a Turkic stone statue that was deliberately (?) buried in the mound, the authors seek to substantiate the reasons for this unusual approach to stone sculpture. Drawing on well-known and close analogies to the situation under analysis, the authors of the article seek to link such processes with some innovative phenomena within the Golden Horde. Research materials: The authors introduce into scholarly circulation completely new archaeological materials found during research in October and November 2020. The novelty of the research: The materials under consideration and their historical and cultural attributes have never been published or discussed previously, except for a volume on the mandatory and complete scientific report on the excavations (the text of descriptions, photos, and illustrations), which has been submitted to the archive of the Institute of Archeology RAS for eternal storage in accordance with the established procedure. Research results: The authors describe the stone statue as according with the Polovtsian funeral rite and compare this description with similar materials from the Don region. A.O. Dobrolyubsky (Odessa) connects the massive change in the traditional orientations of late nomads’ burials with the time of the Golden Horde when the former pre-Mongol funeral rites began to lose their traditional meaning or began to acquire some new meanings. Such innovations were made possible with the appearance of new generations in the Golden Horde (1260–1270s). Subsequently, such a population formed a new syncretic culture under the influence of new ideological influences which gradually replaced the old beliefs and, among other things, led to the rejection of the veneration of statues. Such innovations were accelerated by the process of Islamization among the nomadic population of the Golden Horde. All this led to the spread of the ritual of burial of statues as an obsolete semantic image.